Eksposisi Nalar Tafsir Kiai Sholeh Darat; Telaah Transmisi Keilmuan dan Kontekstualitas Kitab Faidh Ar-Rahman fi Tarjamah Tafsir Kalam Malik ad-Dayyan - Muhammad Hariyadi; Mukhlis Yusuf Arbi (LP2M Universitas PTIQ Jakarta, 2019)
Nusantara, since long time ago, has not only an overwhelming narutal resources, but also a high class human resources. Many Indonesian muslim scholars has an important role in the Arabian penninsula. They were well-known not only by their activities but also written relics. Their bodies must have been buried, but their work has always been read untill now. One the monumental work is in a kind of Tafsir in the begining of 17 century, many Tafsir literatures were started to come out written by Indonesian muslims scholars just like Faidh ar-Rahman by Kiyai Soleh Darat that tended to more brave in making a breakthrough which never exist before. It was an effort to translate the Qur’an into any language other than Arabic, in this case, translating it into Indonesian by using latin language. In muslims point of view, it was an unlawful / bid’ah activity, for Qur’anic translation effort was usually translated in to local languages using Arabic letter, called Pegon. His bravery certainly based on qualified background and transmission of knowledge. This article tries to prove the sanad pathway tracked from many sources and it certainly about the contextality of Faid al-Rahman with the condition of Javanese community at that time